GAMKONORA DAN WAIOLI: BAHASA DALAM KONSTRUKSI IDENTITAS ETNIK - Ninuk Kleden; Imelda Imelda (Kedeputian Bidang Ilmu Sosial dan Kemanusiaan (IPSK-LIPI), 2011)
This paper compares and contrasts Gamkonora language with Waioli languagein west Halmahera, based on linguistic viewpoint. Lexicostatistical studieshave shown that Gamkonora language and Waioli language are two differentlanguages, though the dialect of Gamsungi, a variant of Gamkonora language,is fairly closed to Waioli language. This language variation has a signifcantrole in constructing ethnic identity, particularly if it is connected to anotherlinguistic form such as narrative.Whereas there is language variations in lexicostatistics, one will fnd variousversions in narratives. Both language variation as well as narrative versionscan become ideological persuasion that brings about group sentiments. Theconstruction of ethnic identity comes about owing to the fact that linguisticconditions are in?uenced by political power in the form of social stratifcation.This was the case with Gamsungi people who left the original village ofGamkonora because of the pressure from the upper class. The same thinghappened to people of Talaga who went away from that original villagebecause they refused to pay tax. Islamic in?uence that was established during the Ternate Sultanate and becomes the religion of Gamkonora people, has to face the Christian in?uence embraced by people of Waioli. The paperconcludes that the characteristic of ethnic identity is consolidated by differentdialects and narrative versions as its linguistic underpinning.Keywords: ethic identity, political power, language variation west Halmahera